2017
DOI: 10.18203/issn.2454-5929.ijohns20173031
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological profile of chronic suppurative otitis media in a tertiary care hospital

Abstract: <p class="abstract"><strong>Background:</strong> <span lang="EN-IN">Chronic suppurative otitis media is a disease affecting the middle ear and mastoid cavity, leading to considerable morbidity by causing hearing loss; and even life threatening complications in squamosal type of CSOM, if left untreated over long periods of time. Hence it is imperative to treat the persistent ear discharge in CSOM according to the antibiotic susceptibility of the organisms isolated. </span></p>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 8 publications
2
10
1
Order By: Relevance
“…However the sensitivity to piperacillin tazobactam and ceftazidime was low, compared to similar studies done elsewhere which demonstrated a higher sensitivity to ceftazidime and piperacillin tazobactam. 19,23 However, a good sensitivity was observed to the aminoglycosides and quinolones which again was in contrast to other similar studies done. 25 28% of Pseudomonas aeruginosa isolates were 2 multidrug resistant ,which was quite high.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…However the sensitivity to piperacillin tazobactam and ceftazidime was low, compared to similar studies done elsewhere which demonstrated a higher sensitivity to ceftazidime and piperacillin tazobactam. 19,23 However, a good sensitivity was observed to the aminoglycosides and quinolones which again was in contrast to other similar studies done. 25 28% of Pseudomonas aeruginosa isolates were 2 multidrug resistant ,which was quite high.…”
Section: Discussioncontrasting
confidence: 80%
“…This was similar to the findings of Patel et al and Rangaiah et al in Gujarat and Karnataka respectively. 18,19 The increased incidence in this age group may be due to increased environmental and occupational exposure in this age group. In our study population, 52 were males and 48 were females, indicating a slight male predominance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1416] Diversified psychological care could effectively reduce the anxiety and depression of patients, alleviate their pessimistic and desperate metal status, and finally improve negative emotions. [1719] In the present study, patients with ear, nose, and throat (ENT) symptoms were selected as subjects, and the close and distant impact of comprehensive nursing on patients was subsequently analyzed. The report is presented, as follows.…”
Section: Introductionmentioning
confidence: 99%
“…The swabs were cultured on Blood and MacConkey's agar and overnight incubation was done at 37°C. 6 According to standard microbiological methods, the organisms were isolated. Kirby-Bauer disc diffusion method was performed to identify the antimicrobial susceptibility with the clinical and laboratory standards institute guidelines.…”
Section: Methodsmentioning
confidence: 99%